THE ROLE OF INNOVATIVE TELEMEDICINE TECHNOLOGIES IN DIABETES CARE: A NARRATIVE REVIEW OF METABOLIC, BEHAVIORAL, AND SOCIAL OUTCOMES - Wojtera, Aleksandra; Urantówka, Nina; Węglarz, Aleksandra Karolina; Borowiecka, Patrycja Anna; Adamarczuk, Jagoda Anna; Głuski, Jacek; Miciak, Aleksandra Anna; Kaszowska, Karina Barbara; Dąbrowski, Tomasz Piotr; Kaczmarz-Chojnacka, Karolina; Buziak, Jakub (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Diabetes mellitus remains a major public health challenge worldwide, requiring continuous monitoring, long-term treatment, and active patient participation. Recent advances in telemedicine, continuous glucose monitoring systems, mobile health applications, and artificial intelligence have created new opportunities for remote and personalized diabetes management. Aim: This narrative review evaluated the impact of telemedicine and digital health technologies on metabolic control, treatment adherence, self-management behaviors, and psychosocial outcomes among adults with type 1 and type 2 diabetes mellitus. Materials and Methods: A narrative review of the literature was conducted using keywords in the PubMed database. Recent studies involving adult patients with type 1 and type 2 diabetes were analyzed. Attention was paid to outcomes related to glycated hemoglobin (HbA1c), continuous glucose monitoring metrics, treatment adherence, patient engagement, self-management, and quality-of-life indicators. Results: Most reviewed studies demonstrated that telemedicine interventions significantly improved glycemic control, particularly by reducing HbA1c levels. Digital care models incorporating continuous glucose monitoring increased Time in Range and reduced hyperglycemic exposure. Telemedicine was also associated with improved adherence to treatment recommendations, greater patient engagement, enhanced self-management competencies, and positive psychosocial outcomes, including improved quality of life and reduced diabetes-related distress. The greatest benefits were observed in patients with poor baseline metabolic control and in programs integrating remote monitoring with structured educational support. Conclusions: Telemedicine represents an effective and innovative complement to conventional diabetes care. Digital health technologies facilitate personalized disease management, improve patient participation in therapeutic processes, and may contribute to more accessible and sustainable healthcare delivery.